Answer:
12 + m = 26
Explanation:
Richard spent an unknown amount of dollars at the movie theater, which we're calling m$, and Jordan has spent $12 at the movie theater. All together, they have spent $26.
We can represent the amount of dollars that Richard and Jordan spent as a sum: m + 12
We know that together they spent $26.
We can set these two expressions equal to describe this situation with an equation:
m + 12 = 26
We can also write this as 12 + m = 26, 26 = 12 + m, or 26 = m + 12
The equation is m + 12 = 26, or any of the equivalent equations above.